Pengaruh Flypaper Effect Pada Dana Alokasi Umum (DAU) Terhadap Kinerja Keuangan Pemerintah Daerah Kota Bima Provinsi Nusa Tenggara Barat (NTB) - Savita Fintari (Universitas Terbuka, 2020)
The paper aimed to analyze the influence of the flypaper effect on general allocation funds (DAU) to the financial performance in Bima, West Nusa Tenggara province . Variables used in this research were the general allocation fund (DAU) as independent variabel and the financial performance of local government as dependent variable. This research used a quantitative method. Census was conducted in Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Bima. The data was analyzed using SPSS version 16.0. The finding of the study showed that the flypaper effect of the general allocation funds and the financial performance of local government had a negative and significant relation. The influence of general allocation funds to the financial performance of local government in Bima was 41.2% and the rest 58.8% was the changing of financial performance of local government caused by another variable which was not examined.